RNA-mediated resistance to dengue viruses 1-4 - Adelman, Zachary N., author; Olson, Kenneth E., advisor; Blair, Carol D., advisor; Carlson, Jonathan, committee member; Wilcox, Christine, committee member; Nyborg, Jennifer, committee member (Colorado State University. Libraries, 2000)
Dengue (DEN) viruses (serotypes 1-4) are transmitted to humans by the mosquito Ae. aegypti. DEN virus infection results in morbidity/mortality in 50-100 million people worldwide every year. Efforts to control dengue-caused disease through vaccination or by eliminating the mosquito vector have not been successful. The studies described in this dissertation attempted to generate a state of resistance to DEN viruses in mosquito cells. Resistance strategies were based on the transient or stable expression of DEN-derived RNA. For transient assays, cDNA sequences derived from the genomes of DEN viruses 1-4 were expressed in cultured mosquito cells and Ae. aegypti mosquitoes using a double subgenomic Sindbis virus expression system. dsSIN-infected cells and mosquitoes were challenged with the homologous DEN virus serotype, and the level of virus resistance was determined. Recombinant dsSIN viruses designed to express RNA derived from the C, prM, and NS5 genes were the most effective in establishing virus resistance in mosquito cells. Resistance was established against each of the four DEN virus serotypes. Simultaneous resistance to two DEN virus serotypes was also established in mosquito cells, by inserting DEN genome sequences derived from two DEN viruses into a single recombinant dsSIN virus. cDNA inserts >220 bp were more effective at establishing resistance to DEN viruses than inserts of 105-190 bp. Interference to DEN viruses using recombinant dsSIN viruses was independent of the amount of effector RNA, and was likely due to the presence of dsRNA in the form of a SIN replicative intermediate. For stable assays, transformed mosquito cell lines were developed to express sense, antisense, or dsRNA derived from the DEN-2 prM gene from a constitutive insect virus promoter. Forty-four percent of cell lines designed to express dsRNA were resistant to DEN-2 virus, while <15% of cell lines designed to express sense or antisense RNA alone were resistant to DEN-2 virus. Resistance to DEN-2 virus was not dependent on high levels of transgene mRNA, supporting the hypothesis that a post-transcriptional gene silencing mechanism exists in mosquitoes. These results suggest that permanently transformed, virus-resistant mosquitoes can reasonably be developed with the introduction of a single transgene.
Keywords: microbiology; molecular biology